Translation and Cross-Cultural Adaptation of the Manchester Orofacial Pain Disability Scale - Monira Samaan Kallás; Edgard Michel Crosato; Maria Gabriela Haye Biazevic; Matsuyoshi Mori; Vishal R. Aggarwal (eJournal of Oral Maxillofacial Research)
Objectives: The purpose of the present study was to translate and perform a cross-cultural adaptation of Manchester Orofacial Pain Disability Scale to the Portuguese language. Material and Methods: A synthesis of two independent translations done by bilingual translators whose mother tongue was the Portuguese language began the process of translation. From the synthesis of the translated version and totally blind to the original version, two different non-native English language teachers without dental knowledge translated the questionnaire back to English. The pre-final version was done by an Expert committee: the researchers, two other non-native English language teachers and one native English language speaker. The new questionnaire was then piloted among 8 patients from the target setting that were interviewed to probe it on their perceived meaning of each question. The Manchester Orofacial Pain Disability Scale (MOPDS) thus translated was called Brasil-MOPDS and was validated in 50 patients with Orofacial pain from TMJ and Occlusion clinic ambulatory of São Paulo University School of Dentistry. The Brasil-MOPDS was administered twice by an interviewer (15 - 20 day interval) and once by a second independent interviewer. The Brazilian version of the short form oral health impact profile (OHIP-14) questionnaire and the visual analogue pain scale (VAS) were applied on the same day. Results: Internal consistency (Cronbach’s α = 0.9), inter-observer (ICC = 0.92) and intra-observer (ICC = 0.98) correlations presented high scores. Validity of Brasil-MOPDS compared to OHIP-14 (r = 0.85) and VAS (r = 0.75) shown high correlations. Conclusions: Brasil-MOPDS was successfully translated and adapted to be applied to Brazilian patients, with satisfactory internal and external reliability.